Analisis Optimalisasi Sistem Pendistribusian Air Bersih PDAM Tirta Jaya Kabupaten Pamekasan (Sumber Trasak) - Raihana Azahra Rusadi Putri; Dira Ernawati (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aims to analyse the optimisation of the clean water distribution system by PDAM Tirta Jaya in Pamekasan Regency (Sumber Trasak) by examining the effects of water pressure, distribution service, water quality and water quantity on customer satisfaction. The results show that these four variables contribute only 7.6% to customer satisfaction, while 92.4% is influenced by other factors. The correlations between these variables and customer satisfaction are weak, with Pearson correlation values below 0.5. Furthermore, regression analysis shows that the relationships are insignificant, except for water quality, which has a significant but weak correlation. Based on these results, optimising the clean water distribution system requires a more comprehensive approach that takes into account other factors, such as improving customer service and improving the water distribution infrastructure.